Effects of home‐based lower limb resistance training on muscle strength and functional status in stable Chronic obstructive pulmonary disease patients. Issue 5 (6th February 2018) - Chen, Yi; Niu, Mei'e; Zhang, Xiuqin; Qian, Hongying; Xie, Anwei; Wang, Xiya
Abstract : Aims and objectives: This study aimed to determine the effect of home‐based lower limb resistance training (LLRT) in patients with stable COPD. Background: Pulmonary rehabilitation (PR) in COPD patients has been substantially investigated, but the rehabilitation components differ among studies. Few works have focused on home‐based LLRT. Furthermore, few studies have assessed muscle strength and functional status by isokinetic/isometric extensor muscle peak torque (PT) and five‐repetition sit‐to‐stand test (FTSST), respectively. Design: A randomised controlled design was adopted. Methods: (i) The home‐based LLRT consisted of six sets of lower limb training cycles by self‐gravity resistance and Thera‐band resistance at 8–12RM, 20–30 min/session and 3 sessions/week for 12 weeks. (ii) The intervention group ( n = 25) received routine PR guidance and home‐based LLRT, whereas the control group ( n = 22) received routine PR guidance only. The muscle strengths, FTSST durations, 6‐min walking distances (6MWDs) and COPD assessment test results at enrolment and week 12 were compared. Results: Relative to the baseline findings, all the indexes of muscle strength (isometric extensor muscle PT, isometric extensor muscle PT to body weight ratio [PT/BW], isokinetic extensor muscle PT and isokinetic extensor muscle PT/BW) did not significantly change in the intervention group. Meanwhile, no significant intragroup difference was noted among the indexes of muscle strength (except for isometric extensor muscle PT) in the control group. The FTSST decrease was significant between and within groups. By contrast, the 6MWD significantly increased within both groups, but not between the groups. The COPD assessment tool score decreased significantly within the intervention group. Conclusions: Compared with routine PR guidance, home‐based LLRT can improve not only the muscle strength and exercise endurance but also the lower limb functional status. Relevance to clinical practice: Our developed home‐based LLRT intervention is simple, safe and feasible in stable COPD patients and could hence be promoted in clinical practice.